2021
DOI: 10.54060/jieee/002.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Analysis and Forecasting Using Deep Learning Technique

Abstract: Rainfall forecasting is very challenging due to its uncertain nature and dynamic climate change. It's always been a challenging task for meteorologists. In various papers for rainfall prediction, different Data Mining and Machine Learning (ML) techniques have been used. These techniques show better predictive accuracy. A deep learning approach has been used in this study to analyze the rainfall data of the Karnataka Subdivision. Three deep learning methods have been used for prediction such as Artificial Neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Their proposed deep and wide ANN outperforms the CNN. In another comparison of ANNs, Kanchan and Shardoor (2021) trained ANNs, RNNs, and LSTMs for Karnataka, India. They showed that LSTMs performed the best.…”
Section: D Rainfall Forecastingmentioning
confidence: 99%
“…Their proposed deep and wide ANN outperforms the CNN. In another comparison of ANNs, Kanchan and Shardoor (2021) trained ANNs, RNNs, and LSTMs for Karnataka, India. They showed that LSTMs performed the best.…”
Section: D Rainfall Forecastingmentioning
confidence: 99%
“…The F1-Score uses a precision score and a classifier recall score. F1-Score can be projected using the below formula (5).…”
Section: Model Evaluationmentioning
confidence: 99%
“…Historical data from weather and climate is collected and analyzed to make it predictable. Data such as temperature, humidity, air pressure, evaporation, sunlight, and rainfall levels are used to predict rainfall [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation